2010
DOI: 10.1590/s0100-204x2010000900004
|View full text |Cite
|
Sign up to set email alerts
|

Uso da vespa social Polistes versicolor no controle de desfolhadores de eucalipto

Abstract: Resumo -O objetivo deste trabalho foi determinar os recursos forrageados por Polistes versicolor em área de reflorestamento com eucalipto e identificar as presas forrageadas. No período de janeiro a dezembro de 2007, foram realizadas 24 observações da atividade forrageadora de colônias de P. versicolor presentes em um reflorestamento de eucalipto, em Juiz de Fora, MG, totalizando 240 horas de registros. Durante as dez horas de observação diária, foram registrados e qualificados, a cada 30 minutos, os retornos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 4 publications
(9 reference statements)
4
38
0
10
Order By: Relevance
“…There was a positive correlation between abundance and the warmest times of the day (r = 0.7635; P = 0.0062). These results corroborate studies on social wasp foraging, in which the activity peak of wasps was observed in the warmest times of the day (Rezende et al 2001;Elisei et al 2010;Bichara Filho et al 2010;Castro et al, 2011). There was no wasp visit from 14:30 to 17:00h.…”
Section: Short Notesupporting
confidence: 86%
“…There was a positive correlation between abundance and the warmest times of the day (r = 0.7635; P = 0.0062). These results corroborate studies on social wasp foraging, in which the activity peak of wasps was observed in the warmest times of the day (Rezende et al 2001;Elisei et al 2010;Bichara Filho et al 2010;Castro et al, 2011). There was no wasp visit from 14:30 to 17:00h.…”
Section: Short Notesupporting
confidence: 86%
“…Plt. versicolor is another species with a wide distribution in Brazil (Richards, 1978), which has been suggested as a biological control agent in certain crops, such as for control of the eucalyptus defoliator (Elisei et al, 2010). A colony of Plt.…”
Section: Social Wasps Community In Ipeúna -Spmentioning
confidence: 99%
“…These hymenopterans present predatory habit on a wide number of insects, providing animal protein used to feed the offspring. About 90 to 95% of the preys captured by social wasps are caterpillars (Prezoto et al 1994;Giannotti et al 1995;Prezoto et al 2006;raveret-richter 2000;eLisei et al 2010). Due to this behavior, the social wasps play an important role on the population control of species in the ecosystems, reducing the chances to appear great populations of preys, being as one potential biological controller of agricultural plagues.…”
Section: _____________________________________mentioning
confidence: 99%